Innate Lymphoid Cells in Protection, Pathology, and Adaptive Immunity During Apicomplexan Infection - Ivanova, Daria L.; Denton, Stephen L.; Fettel, Kevin D.; Sondgeroth, Kerry S.; Munoz Gutierrez, Juan; Bangoura, Berit; Dunay, Ildiko R.; Gigley, Jason P. (Frontiers in Immunology, 2019)
Apicomplexans are a diverse and complex group of protozoan pathogens including Toxoplasma gondii, Plasmodium spp., Cryptosporidium spp., Eimeria spp. and Babesia spp. They infect a wide variety of hosts and are a major health threat to humans and other animals. Innate immunity provides early control and also regulates the development of adaptive immune responses important for controlling these pathogens. Innate immune responses also contribute to immunopathology associated with these infections. Natural killer (NK) cells have been for a long time known to be potent first line effector cells in helping control protozoan infection. They provide control by producing IL-12 dependent IFNγ and killing infected cells and parasites via their cytotoxic response. Results from more recent studies indicate that NK cells could provide additional effector functions such as IL-10 and IL-17 and might have diverse roles in immunity to these pathogens. These early studies based their conclusions on the identification of NK cells to be CD3-, CD49b+, NK1.1+ and/or NKp46+ and the common accepted paradigm at that time that NK cells were one of the only lymphoid derived innate immune cells present. New discoveries have lead to major advances in understanding that NK cells are only one of several populations of innate immune cells of lymphoid origin. Common lymphoid progenitor derived innate immune cells are now known as innate lymphoid cells (ILC) and comprise three different groups, group 1, group 2, and group 3 ILC. They are a functionally heterogeneous and plastic cell population and are important effector cells in disease and tissue homeostasis. Very little is known about each of these different types of ILCs in parasitic infection. Therefore, we will review what is known about NK cells in innate immune responses during different protozoan infections. We will discuss what immune responses attributed to NK cells might be reconsidered as ILC1, 2 or 3 population responses. We will then discuss how different ILCs may impact immunopathology and adaptive immune responses to these parasites.